Ethics as worship : the pursuit of moral discipleship - Liederbach, Mark; Lenow, Evan (New Jersey P&R Publishing, 2021)
"Ethics as Worship examines the foundations and application of Christian ethics, offering an ethical system that emphasizes the worship of God as motivation, method, and goal of the ethical endeavor"--
Includes bibliographical references (pages 703-733) and index.
Keywords: Worship; Christian ethics